EFEKTIFITAS PENGGUNAAN APLIKASI DARING DAN VIDEO CONFERENCE MATERI SYSTEM DESIGN AND ANALISYS METHOD (SDAM) MASA PANDEMI - Salma Nofri Yanti; M. Yemmardotillah (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2021)
The phenomenon of the Covid-19 virus that spreads to Indonesia which causes the death rate to increase, Covid-19 has an impact on the application of learning patterns in the world of education. This also occurs in the course of the study program system design and analysis method (SDAM) for Computer and Information Engineering Education, Tarbiyah, IAIN Bukittinggi. The process of delivering lecture material switches from face-to-face (offline) to fully digital (online) by utilizing educational-based applications, namely Scoology and Zoom Meetings. The purpose of this study was to determine the level of understanding of students in using the application. The research method used is a survey method which was conducted online by taking samples of students in the System Design and Analysis Method (SDAM) course. The expected result of this research is that it can be used as a benchmark in the development of the online teaching and learning process in the coming semester